Variação linguística no ensino de Língua Portuguesa para o 8º ano do Ensino Fundamental - Silva, Maria Elizabete Ávila (2024)
The present research on the contributions of studies on linguistic variation to the teaching of Portuguese in the final years of elementary education aims to contribute to the understanding of this phenomenon, as well as to present its importance for the teaching of Portuguese in accordance with new educational concepts. In this regard, we utilized various studies related to the topic through a bibliographic research to develop a study on linguistic variation, aiming to reduce writing and agreement difficulties in texts produced by 8th-grade students. In this research, actions were taken based on the appreciation and analysis of the phenomenon of linguistic variation in different genres (comic strips, caricatures, poetry, music, films, documentaries) and its impact on the school context and society. It is important to highlight that the research focused on both writing and orality. To this end, a pedagogical activity book was created with the aim of proposing activities directed towards a contextualized grammar teaching articulated with linguistic practices. The theoretical basis for the development of this study was the various researches on the subject from the perspective of variational and educational Sociolinguistics. Thus, this work took as theoretical references Bortoni-Ricardo (2014-2017); Bagno (2007-2014), Cardoso; Cobucci (2014), Labov (2008), Lima (2014); Morais (2015); Marques; Baronas (2015), Razky; Feitero (2015), Monteiro (2000), Rocha (2014), among others. Based on these studies, we observed that there has been significant progress in the treatment of the phenomenon of linguistic variation in many educational materials and, consequently, in its approach in the classroom, although some inadequacies in how this topic is addressed still occur.